2001
DOI: 10.1074/jbc.m010481200
|View full text |Cite
|
Sign up to set email alerts
|

Toll-like Receptor-2 Mediates Treponema Glycolipid and Lipoteichoic Acid-induced NF-κB Translocation

Abstract: Recently Toll-like receptors (TLRs) have been found to be involved in cellular activation by microbial products, including lipopolysaccharide, lipoproteins, and peptidoglycan. Although for these ligands the specific transmembrane signal transducers TLR-4, TLR-2, or TLR-2 and -6 have now been identified, the molecular basis of recognition of lipoteichoic acids (LTAs) and related glycolipids has not been completely understood. In order to determine the role of TLRs in immune cell activation by these stimuli, exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
141
0
2

Year Published

2002
2002
2016
2016

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 209 publications
(150 citation statements)
references
References 68 publications
7
141
0
2
Order By: Relevance
“…Taken together, we found that Tm-Gp, in contrast to the extracts of small-sized Treponema species [18,19], does not activate host cells but is capable of inhibiting intracellular signaling induced by LPS and PGN by blocking the function of LBP and/or CD14. In such immunomodulating active components, marginal variations of the detailed structures, such as the variations of acylation and phosphorylation patterns in the lipid A of LPS, are well-known to be closely related to their effects [43].…”
Section: Inhibitory Effect Of a Glycoconjugate On Cell Activation Andmentioning
confidence: 68%
See 3 more Smart Citations
“…Taken together, we found that Tm-Gp, in contrast to the extracts of small-sized Treponema species [18,19], does not activate host cells but is capable of inhibiting intracellular signaling induced by LPS and PGN by blocking the function of LBP and/or CD14. In such immunomodulating active components, marginal variations of the detailed structures, such as the variations of acylation and phosphorylation patterns in the lipid A of LPS, are well-known to be closely related to their effects [43].…”
Section: Inhibitory Effect Of a Glycoconjugate On Cell Activation Andmentioning
confidence: 68%
“…Glycolipids from small-sized Treponema species have been shown to exhibit activating ability upon host cells [18,19]. In contrast, Tm-Gp exhibited no activation of Mono Mac 6 cells at the highest concentration tested (100 ?…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…These genes include TLR2 and LY96. TLR2 is known to be upregulated in response to peptidoglycan, lipoteichoic acid, 29 and bacterial lipoproteins 30 or LPS. TLR4 is activated by the LPS of Gram-negative bacteria 31 and LY96 is a protein associated with this receptor.…”
Section: Discussionmentioning
confidence: 99%